Sexual orientation and gender identity: review of concepts, controversies and their relation to psychopathology classification systems - Moleiro, Carla; Pinto, Nuno (Frontiers in Psychology, 2015)
Numerous controversies and debates have taken place throughout the history of psychopathology (and its main classification systems) with regards to sexual orientation and gender identity. These are still reflected on present reformulations of gender dysphoria in both DSM and ICD, and in more or less subtle micro-aggressions experienced by lesbian, gay, bisexual and trans patients in mental health care. The present paper critically reviews this history and current controversies. It reveals that this deeply complex field contributes (i) to the reflection on the very concept of mental illness; (ii) to the focus on subjective distress and person-centered experience of psychopathology; and (iii) to the recognition of stigma and discrimination as significant intervening variables. Finally, it argues that sexual orientation and gender identity have been viewed, in the history of the field of psychopathology, between two poles: gender transgression and gender variance/fluidity.